Cardiovascular toxicity associated with angiogenesis inhibitors: A comprehensive pharmacovigilance analysis based on the FDA Adverse Event Reporting System database from 2014 to 2021 - Wang, YanFeng; Cui, Chanjuan; Ren, Xiayang; Dong, Xinran; Cui, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background The profiles of cardiovascular toxicity associated with angiogenesis inhibitors, including intravenous monoclonal antibodies (mAbs) and oral tyrosine kinase inhibitors (TKIs), targeting vascular endothelial growth factor (VEGF) remain poorly elucidated in real-world settings. This pharmacovigilance analysis aimed to comprehensively investigate the frequency, spectrum, timing, and outcomes of cardiovascular toxicities associated with angiogenesis inhibitors and to explore the differences in such patterns between mAbs and TKIs. Methods Disproportionality analysis was performed by leveraging reports from the FDA Adverse Event Reporting System (FAERS) database from 2014 to 2021. Cardiovascular adverse events (AEs) were grouped into nine narrow categories using the Standardized Medical Dictionary for Regulatory Activities (MedDRA) Queries (SMQs). Reporting odds ratio (ROR) and information components (ICs) were calculated with statistical shrinkage transformation formulas and a lower limit of 95% confidence interval (CI) for ROR (ROR025) > 1 or IC (IC025) > 0, with at least three reports being considered statistically significant. Results A total of 757,577 reports of angiogenesis inhibitors and 70,668 (9.3%) reports of cardiovascular AEs were extracted. Significant disproportionality was detected in angiogenesis inhibitors for cardiovascular AEs (IC025/ROR025 = 0.35/1.27). Bevacizumab (31.8%), a mAb, presented the largest number of reports, followed by sunitinib (12.4%), a TKI. Hypertension (SMQ) was detected with the strongest signal value (IC025/ROR025 = 1.73/3.33), followed by embolic and thrombotic events (SMQ) (IC025/ROR025 = 0.32/1.26). Hypertension showed the shortest time to onset with a median (interquartile range) value of 23 (8, 69) days, while embolic and thrombotic events had the longest value of 51 (16, 153) days. Notably, hypertension presented the lowest proportions of death and life-threatening events (10.9%), whereas embolic and thrombotic events posed the highest (29.3%). Furthermore, both mAbs (IC025/ROR025 = 0.47/1.39) and TKIs (IC025/ROR025 = 0.30/1.23) showed increased cardiovascular AEs. Hypertension was detected in both agents (IC025/ROR025 = 1.53/2.90 for mAbs and IC025/ROR025 = 1.83/3.56 for TKIs) with a shorter time to onset of 17 (6, 48) days for TKIs than mAbs of 42 (14, 131) days. By contrast, embolic and thrombotic events were detected for mAbs (IC025/ROR025 = 0.90/1.87) without TKI (IC025/ROR025 = −0.08/0.95). Conclusion Angiogenesis inhibitors were associated with increased cardiovascular toxicity with a discrepancy between intravenous mAbs and oral TKIs, deserving distinct monitoring and appropriate management.